Bimatoprost/timolol fixed combination versus latanoprost in treatment-naïve glaucoma patients at high risk of progression: a pilot study - Gutierrez-Diaz E (Dove Medical Press, 2014)
Esperanza Gutierrez-Diaz,1 Jose Silva Cotta,2 Francisco J Muñoz-Negrete,3 Consuelo Gutierrez-Ortiz,4 Robert J Morgan-Warren,5 John Maltman5 On behalf of the GIFT study group1Department of Ophthalmology, Hospital Doce de Octubre, Universidad Complutense, Madrid, Spain; 2Department of Ophthalmology, Hospital de São João, Porto, Portugal; 3Department of Ophthalmology, Hospital Ramón y Cajal, IRYCIS, Universidad Alcalá, Madrid, Spain; 4Department of Ophthalmology, Hospital Universitario Príncipe de Asturias, Madrid, Spain; 5Medical Affairs, Allergan Holdings Ltd, Marlow, UKObjective: To compare a fixed combination of 0.03% bimatoprost and 0.5% timolol (BTFC) with latanoprost monotherapy (LM) in treatment-naïve patients with open-angle glaucoma (OAG) and risk factors for glaucomatous progression.Methods: Patients were enrolled at 15 sites in Spain and Portugal, and were randomized 1:1 to BTFC or LM. Patients instilled one drop of medication once per day at 8 pm for 12 weeks. The primary outcome was change in intraocular pressure (IOP) at 12 weeks.Results: Of 81 patients enrolled, 43 were randomized to BTFC and 38 to LM. Mean (SD) change in IOP from baseline to 12 weeks was significantly greater for BTFC than for LM: -13.5 mmHg (4.48) versus -11.4 mmHg (3.19), respectively (P=0.003). Similarly, at 12 weeks, significantly more BTFC patients than LM patients had IOP reductions of ≥40% (74.4% versus 47.4%, P=0.015) or ≥50% (46.5% versus 15.8%, P=0.003). Adverse events were more frequent with BTFC than with LM (33 versus 13 events), but most were mild in severity. The only serious adverse event (colon cancer) was adjudged unrelated to the study medication.Conclusion: BTFC was effective and well tolerated in treatment-naïve patients with OAG at high risk of progression.Keywords: open-angle, fixed combinations